FERMT2 links cortical actin structures, plasma membrane tension and focal adhesion function to stabilize podocyte morphology - Yasuda-Yamahara, M.; Rogg, M.; Frimmel, J.; Trachte, P.; Helmstaedter, M.; Schroder, P.; Schiffer, Mario; Schell, C.; Huber, T. B. (Matrix Biology, 2018)
Simplification and retraction of podocyte protrusions, generally termed as foot process effacement, is a uniform pathological pattern observed in the majority of glomerular disease, including focal segmental glomerulosclerosis. However, it is still incompletely understood how the interaction of cortical actin structures, actomyosin contractility and focal adhesions, is being orchestrated to control foot process morphology in health and disease. By uncovering the functional role of fermitin family member 2 (FERMT2 or kindlin-2) in podocytes, we provide now evidence, how cell-extracellular matrix (ECM) interactions modulate membrane tension and actomyosin contractility. A genetic modeling approach was applied by deleting FERMT2 in a set of in vivo systems as well as in CRISPR/Cas9 modified human podocytes. Loss of FERMT2 results in altered cortical actin composition, cell cortex destabilization associated with plasma membrane blebbing and a remodeling of focal adhesions. We further show that FERMT2 knockout podocytes have high levels of RhoA activation and concomitantly increased actomyosin contractility. Inhibition of actomyosin tension reverses the membrane blebbing phenotype. Thus, our findings establish a direct link between cell-matrix adhesions, cortical actin structures and plasma membrane tension allowing to better explain cell morphological changes in foot process effacement.
EVALuna2:34539